2018
DOI: 10.1107/s2052252517017833
|View full text |Cite|
|
Sign up to set email alerts
|

Protein crystal lattices are dynamic assemblies: the role of conformational entropy in the protein condensed phase

Abstract: Until recently, the occurrence of conformational entropy in protein crystal contacts was considered to be a very unlikely event. A study based on the most accurately refined protein structures demonstrated that side-chain conformational entropy and static disorder might be common in protein crystal lattices. The present investigation uses structures refined using ensemble refinement to show that although paradoxical, conformational entropy is likely to be the major factor in the emergence and integrity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Together with the high crystallization enthalpy, entropy changes ensure the negative values of Gibbs free energy required for spontaneous crystallization are attained (for more details see [12,13]). The conformational entropy of residues involved in crystal contact has been recently reconsidered [14]. Simultaneously, study of hydrogen bonds, van der Waals contacts and electrostatic interactions has shown that hydrogen-mediated van der Waals interactions are the dominant force that maintains protein crystal lattice integrity.…”
Section: Thermodynamic Basis Of Ebde and Definition Of Protein-to-watmentioning
confidence: 99%
“…Together with the high crystallization enthalpy, entropy changes ensure the negative values of Gibbs free energy required for spontaneous crystallization are attained (for more details see [12,13]). The conformational entropy of residues involved in crystal contact has been recently reconsidered [14]. Simultaneously, study of hydrogen bonds, van der Waals contacts and electrostatic interactions has shown that hydrogen-mediated van der Waals interactions are the dominant force that maintains protein crystal lattice integrity.…”
Section: Thermodynamic Basis Of Ebde and Definition Of Protein-to-watmentioning
confidence: 99%
“…In the case of protein crystals, lattice molecules can undergo rather rapid rocking motions, 19 and the molecular contacts are thought to be dynamic. 20 Unlike most inorganic solids, protein crystals also show a remarkable ability to incorporate a wide variety of relatively large particles, such as homologous microcrystals, 21 foreign nanocrystals, 22 or polymer fibres, 23 without significant disturbance the long-range order of the lattice periodicity of the crystals. This accommodating capacity of protein crystals has been attributed to the prevailing noncovalent water-mediated lattice contacts.…”
Section: Introductionmentioning
confidence: 99%
“…This accommodating capacity of protein crystals has been attributed to the prevailing noncovalent water-mediated lattice contacts. 20 It has recently been demonstrated that the adaptive properties of macromolecular lattices can be further improved when the lattices are integrated into a hydrogel network that permits the protein crystals to expand isotopically and to return to their original volume while retaining their periodic order. 24 However, in a quite contradictory manner, perfectly shaped macroscopic protein crystals often display poor diffraction properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several researchers have investigated the roles of electrostatic energy and entropy or van der Waals force in the interactions among nanostructures such as the binding of nanoparticles or nanowires, protein folding, and flow viscosity in nanofluids [44][45][46]. However, the collective impact of these factors on the binding and release among biomolecules have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%